REMINDER IMPULSE BUYING PADA GAME ONLINE THE ANTS UNDERGROUND KINGDOM - Eka Adiputra; Ari Kuntardina; Waghfirotul Afkar; Nik Amah (CAPITAL: Jurnal Ekonomi dan Manajemen, 2025)
Impulse buying triggered by reminders can happen to game players. This is influenced by several factors such as hedonic shopping motivation and availability of money. This research aims to determine whether there is an influence between hedonic shopping motivation and availability of money on impulse buying reminders in the online game The Ants Underground Kingdom with research objects in the IDE (Indonesia Eksplore) community. Quantitative research using saturated sampling techniques, namely using all members of the community as samples. Data was collected through a questionnaire given to 70 members of the IDE community. Data analysis using multiple linear regression. The analysis shows that hedonic shopping motivation has a significant effect on impulse buying reminders. Meanwhile, availability of money has an insignificant influence on impulse buying reminders. In conclusion, players who have hedonic shopping tendencies will tend to carry out impulse buying which is triggered by reminders. Whether or not funds are available can trigger impulse buying reminders. This can be caused by the player's level of addiction to the game.